The Validity and Reliability of Online Examinations in the State Universities of Sri Lanka: An Empirical Study - Abeywickrama, Rohan; Dissanayake, Thilini (Andalas International Journal of Socio-Humanities, 2022)
The aim of the current study is to examine the validity and reliability of online examinations through undergraduates’ and lecturers’ perceptions and identify the ways in which online examinations can be more focused and effective. To this end, a questionnaire including both qualitative and quantitative inquiries were administered among forty-five undergraduates and fifteen lecturers of three state universities in Sri Lanka. Thematic Analysis and SPSS software were used to analyze qualitative and quantitative data respectively. Findings of the study indicate that 80% of the undergraduates and lecturers preferred traditional examinations to online assessments given its flexibility, validity, and fairness. Majority of the lecturers encountered issues during online examinations, thus they reported the need of improving the methods and strategies of online assessments in a way they measure undergraduates’ performance accurately. Moreover, undergraduates’ social, economic, technological, and psychological issues also hindered the effectiveness of online examination to a considerable extent. The results of online examinations cannot be regarded as valid and reliable because they were unable to evaluate undergraduates’ learning outcomes as accurately as onsite examinations. The study has implications for the undergraduates, test administrators, lecturers, and the university management.